Exploring Students Perception and ICT Use in Indonesian High Schools - Anton Suratno; Emilia Ninik Aydawati (Celt: A Journal of Culture, English Language Teaching & Literature, 2016)
The recent spread of technological innovation along with the sophistication of the ICT gadgets have shapped and transformed the realm of learning and teaching including in that of English Language. Alongside, ICT has become more and more inextricable part of human businesses and put a higher level of demand for technological literacy in the part of English learners in order for them to be convident in the digital era membership and participation. This study surveyed 400 high school students as regards: (a) their ICT gadgets perceived ownership; (b) their day-to-day outside and in-school use and; (c) their activities using ICT gadgets for English learning. Findings from the descriptive analyses of the mixed-method study, disclose the positive perception about the gadget ownership. Interestingly, the current study also discovers that there has been a mismatch between the positively perceived ownership of the ICT gadgets and the real day-to-day use as facilitative media for learning, in particular as a useful aids for English language learning. Focusing on the result discussion, issues with regard to discrepancies in the provision of infrastructures and the lack of the support system by school institutions emerge from the FGD analysis highlighting the importance for all decision makers, school institutions, and teachers to consciously start doing something about it. By highlighting the pivotal role of the technology, the researcher suggested a real action for responding to the call for a change in both policy makers and institutonal levels to start integrating the technology into the school curricula.